Interference in the Collective Electron Momentum in Double Photoionization of H2 - Kreidi, K.; Akoury, D.; Jahnke, T.; Weber, Th.; Staudte, A.; Schöffler, M.; Neumann, N.; Titze, J.; Schmidt, L. Ph. H.; Czasch, A.; Jagutzki, O.; Costa Fraga, R. A.; et al. (My University, 2008)
We investigate single-photon double ionization of H2 by 130 to 240 eV circularly polarized photons. We find a double slitlike interference pattern in the sum momentum of both electrons in the molecular frame which survives integration over all other degrees of freedom. The difference momentum and the individual electron momentum distributions do not show such a robust interference pattern. We show that this interference results from a non-Heitler-London fraction of the H2 ground state where both electrons are at the same atomic center.